Flexural and shear characteristics of bio-based sandwich beams made of hollow and foam-filled paper honeycomb cores and flax fiber composite skins. (August 2020) - Fu, Yuchen; Sadeghian, Pedram
Abstract: In this paper, bio-based sandwich panels made of fiber-reinforced polymer (FRP) skins and two types of paper honeycomb core (namely, hollow and foam-filled) with three different thicknesses (namely, 6 mm, 12 mm, and 25 mm) were studied. Flax FRP composites made of a unidirectional plant-based flax fabric and bio-based epoxy resin (30% bio content) were used for the skins. The panels were cut into a total of 36 sandwich beam specimens with the width of 50 mm and tested under four-point bending with two span configurations to characterize the flexural and shear stiffness of the panels. The specimens with foam-filled paper honeycomb cores showed a higher load capacity than those with hollow honeycomb, however their stiffnesses were not fundamentally different. Major non-linearity was observed in the load-deflection and load-strain behavior of the specimens. An analytical model was successfully developed based on the non-linearity of the skins in tension/compression and the core in shear to predict the non-linear behavior of the specimens. A parametric study was performed on different geometrical parameters and it was shown that contribution and bending and shear changes and it can be engineered to achieve desirable strength and stiffness. Overall, the bio-based sandwich panels can be used for interior walls, doors, and furniture in building application with much less impact on the environment in comparison with their synthetic counterparts. Highlights: Small-scale sandwich beams made of hollow and foam-filled paper honeycomb cores and flax fiber composite skins were tested under bending. Bending and shear stiffness of the sandwich composites were characterized. Major non-linearity was observed in the load-deflection and load-strain behavior of the specimens. An analytical model was developed to predict the non-linear behavior of the sandwich composites. A parametric study was performed on core thickness, skin thickness, and span length of the sandwich beams.